Ludificação do ensino da programação: um caso de estudo - Jorge Adolfo David Castro Monteiro (2017)
With this dissertation it is intended to find a solution to the existing problem among the students that get into the higher education, regarding the teaching and learning of programming. Many of these students have a heterogeneous experience in programming practice, wich makes the speed at which the content taught in the classes be it appropriate for only the part of the students, which may cause distress or boredom.The goal is to attend to the needs of each student, individualizing their course in the curricular unit and increasing their motivation and effectiveness of this process. Therefore, a case study was carried out applied to Fundamentals of Programming curricular unit of the 1º year, 1º semester of MIEIC of Engineering Faculty of Porto University, where gamification elements and techniques were used to create a system that can be implemented on moodle platform. This system is regulated by a scoring and level system to foster students's progression in the discipline at their own pace and according to their skills in each moment. As the students moves forward in the content, new challenges that should be completed are unblocked so as new resources that they can utilizes to progress in the way that suits them best in the unit. The concept of stickers album is introduced as a way of engaging and encourage more the students in the activities of programming learning. The locked stickers will have a shading in shades of gray and will indicate the necessary goals to unlock them. The studens can collect stickers and try to complete the sticker álbum, participating in the sytem and getting good performance and results. After unlocking, the stickers will adopt their original colors.The evaluation of the work was performed through a survey to the students that attend this curricular unit before, to analyse their opinion regarding the old and the new gamified system. It was also made a semi-Structured interview to specialists in the fields of programming teaching to get a more qualitative information on the potentiality and impact of this system, after being implemented, in the motivation and students's result.